2018
DOI: 10.18203/2319-2003.ijbcp20184333
|View full text |Cite
|
Sign up to set email alerts
|

A survey of knowledge, attitude and practice of adverse drug reaction monitoring among doctors in Western Odisha region

Abstract: Background: Adverse drug reactions (ADRs) are the major cause of drug related morbidity and mortality. Pharmacovigilance is the science that plays an important role in the reduction of ADRs. Voluntary reporting of ADRs by healthcare professionals is an important tool in the success of pharmacovigilance program, but the same are scantly reported due to lack of awareness and knowledge among the physicians. So, the present study was conducted to evaluate the knowledge, attitude and practice (KAP) regarding ADR re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
1
0
0
Order By: Relevance
“…Knowledge regarding ADR reporting is very important for physicians. The result showed that majority (61.43%) of the physicians had adequate knowledge (Knowledge score > 66%) related to ADR reporting which is in correspondence with studies conducted in Karachi Pakistan and Western Odisha India 16,17 . Knowledge regarding ADR reporting is very important for physicians.…”
Section: Discussionsupporting
confidence: 77%
“…Knowledge regarding ADR reporting is very important for physicians. The result showed that majority (61.43%) of the physicians had adequate knowledge (Knowledge score > 66%) related to ADR reporting which is in correspondence with studies conducted in Karachi Pakistan and Western Odisha India 16,17 . Knowledge regarding ADR reporting is very important for physicians.…”
Section: Discussionsupporting
confidence: 77%